Cardiac arrhythmias related to psychiatric medication - Elsayed, M.; Freudenmann, R. W.; Schönfeldt-Lecuona, C.; Connemann, B. J.; Gahr, M. (Nervenheilkunde, 2017)
This narrative review summarizes current available information about cardiac arrhythmias (QT prolongation, Torsade de pointes Tachycardia [TdP], sudden cardiac death) associated with psychiatric medication. Among the most commonly used antipsychotics, amisulpride and ziprasidone are most frequently associated with TdP. Treatment with some antidepressants (SSRIs, tricyclic antidepressants) is associated with a 5- to 6-fold increase in the incidence of out-of-hospital cardiac arrest. Lithium is associated with bradycardia, T-wave changes and AV-block; anxiolytics of the benzodiazepine group do usually not have cardiac side effects. The combination of multiple drugs (including medications from general medicine) that prolong the QT interval has a particularly high cardiac risk.
Keywords: Psychopharmacology; torsade de pointes; achycardia; sudden cardiac arrest; QT prolongation